PENGARUH HARGA DAN SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN GAS LPG 3 KG PADA PANGKALAN BUMI PELITA ASRI (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
The purpose of this test is to examine: (1) how does the price affect the sales volume of 3 Kg LPG gas for the Bumi Pelita Asri Base, (2) how does the distribution channel influence the sales volume of 3 Kg LPG gas for the Bumi Pelita Asri Base. The sample in this test is a customer or consumer who buys 3 Kg LPG Gas at Pangkalan Bumi Pelita Asri with a total of 73 respondents using a purposive sampling technique. The instrument in this test is a questionnaire that has been tested for validity and reliability using Alpha Cronbach. Thedata analysis method used for testing is multiple linear regression by applying the statisticaldata processing program SPSS (Statistical Package for The Social Science ) for Windows Release 25.0. The test results based on multiple linear tests show that: (1) A constant value (a) of 0.599 indicates that when the independent variable (price, distribution channel) is constant (x=0), then the consumers of the 3 KG LPG Gas Base Bumi Pelita Asri those who become respondents are able to increase sales volume in the continuity of business at the company. (2) The results of multiple linear regression testing show that the price variable has a regression coefficient of 0.133 with a significance value of 0.013. This value is smaller than the probability value of 5% (0.05). Thus the first hypothesis which states that price has a positive effect on business continuity is accepted (H1 is accepted). (3) The results of multiple linear regression testing show that the distribution channel variable has a regression coefficient of 0.425 with a significance value of 0.000. This value is smaller than the probability value of 5% (0.05). Thus the second hypothesis which states that distribution channels have a positive effect on sales volume is accepted.
Keywords: Gas LPG 3 KG; Effect of Price; Distribution System